2012
DOI: 10.1590/s1415-43662012001200014
|View full text |Cite
|
Sign up to set email alerts
|

Biossorção de cobre utilizando-se o mesocarpo e o endocarpo da macadâmia natural e quimicamente tratados

Abstract: 2+). The chemical changes in the biosorbent with sodium hydroxide (NaOH) and with NaOH and citric acid were evidenced by infrared spectroscopy by the appearance of peaks in 1710 and 1420 cm -1 and by scanning electron microscopy, observed an increase of roughness on the surface. The best results of the adsorption were observed in mesocarp modified with NaOH, in pH equal to 5. An equilibrium time adsorbent -adsorbate was 140 min, in addition, the system followed a kinetic model of pseudo-second order and the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
3
0
5
Order By: Relevance
“…About the kinetics models, there is a reduction in the adsorptive capacity of dregs over time, is probably a better fit to the beginning of the process since it is characterized as physical adsorption. The adsorption of metals at alkaline conditions is generally low since certain chemical groups only deprotonate at low pH values, allowing the binding of metals on the adsorbent surface (Boas et al, 2012). Decreases in removal percentage at high adsorbent dosages may be related to the saturation of adsorption sites (Alshameri et al, 2014), which was also reported by Fidelis (2015).…”
Section: Discussionmentioning
confidence: 84%
“…About the kinetics models, there is a reduction in the adsorptive capacity of dregs over time, is probably a better fit to the beginning of the process since it is characterized as physical adsorption. The adsorption of metals at alkaline conditions is generally low since certain chemical groups only deprotonate at low pH values, allowing the binding of metals on the adsorbent surface (Boas et al, 2012). Decreases in removal percentage at high adsorbent dosages may be related to the saturation of adsorption sites (Alshameri et al, 2014), which was also reported by Fidelis (2015).…”
Section: Discussionmentioning
confidence: 84%
“…The biosorbent was characterized by determining the point of zero charge (PZC) according to the methodology proposed by Boas et al (2012), analysis by scanning electron microscopy (SEM) and Fourier transform infrared spectrum (FTIR).…”
Section: Methodsmentioning
confidence: 99%
“…A presença de poros e rugosidades na superfície do resíduo proporciona uma boa capacidade de biossorção o que é corroborado por vários outros estudos. [28][29][30] Determinação do ponto de carga zero (pH PCZ ) O ponto de carga zero (pH PCZ ) para o pó do caroço de açaí foi estimado graficamente em torno de 5,45, valor aproximado foi obtido por Gonçalves Jr. 28…”
Section: Caracterização Morfológicaunclassified